Animal Abuse in Ryan Baldock's Internet Panhandling - Dherina Stevani (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2022)
This study discusses how internet panhandling and animal abuse depicted in TikTok live streaming. This study also explores the viewer’s respond from Ryan Baldock Martin live streaming using a cultural study approach. This study aims to find a side effect from TikTok live streaming: Internet Panhandling from the viewers’ eyes and reaction to live streaming Ryan Baldock Martin. Julian Steward, Lawrence Grossberg and Stuart Hall theory serve as theoretical cultural studies: Ecological Cultural Study, Circuit of Culture and Audience Reception. From circuit of culture theory by Lawrence Grossberg, the author only using two from five elements there are representation and identification. While theory by Stuart Hall, can be classified into three categories there are dominant, negotiated, and oppositional reading. This study using a qualitative method approached circuit of culture and audience reception theory. The author observing and identifies this study with viewers’ respond TikTok whose comment section and stich videos by Ryan Baldock Martin. The result of this study conducts that viewers’ opinion can be highlight that live stream of Ryan Baldock Martin can damage the image of TikTok, image of content creator, and bad influence to social media users.Keywords: Internet Panhandling, TikTok, live streaming, animal abuse